The role of multiple anatomical scenarios in plan optimization for carbon ion radiotherapy of pancreatic cancer. (November 2022) - Molinelli, Silvia; Vai, Alessandro; Russo, Stefania; Loap, Pierre; Meschini, Giorgia; Paganelli, Chiara; Barcellini, Amelia; Vitolo, Viviana; Orlandi, Ester; Ciocca, Mario
Highlights: Planning on multiple anatomic scenarios could improve CIRT robustness for pancreatic cancer. The PRV approach fails in predicting duodenum position along the RT course. Efficient online adaptation is needed to guarantee CIRT quality for pancreatic cancer. Abstract: Purpose /objective: To quantify benefits of robust optimization on multiple 4DCT acquisitions combined with off-line treatment adaptation for neoadjuvant carbon ion therapy (CIRT) of pancreatic cancer. Material/methods: For 10 previously treated patients, 4DCTs were acquired around −15 (CTPlan ), −5 (RE1 ), −1 (RE2 ) and +6 (RE3 ) days from RT start. Treatment plans were newly optimized to a dose prescription of 38.4 Gy(RBE) (8 fractions) with a constraint of 38 Gy(RBE) to 1% of the gastrointestinal organs at risk volume (D1% ). Three strategies were tested: (A) robust optimization on CTPlan maximum exhale (0Ex) with 3 mm set-up, 3% range uncertainty, including 30%-inhale; (B) addition of the RE1 -0Ex scenario; (C) plan recalculation at each REi and adaptation (RPi ) according to deviation thresholds from clinical goals. The cumulative variation of target coverage and GI-OARs doses was evaluated. Duodenum contours of all 4DCTs of each patient were registered on CTPlan -0Ex. The capacity of pre-RT acquisitions to predict duodenum position was investigated by computing the intersection of contours at CTplan, RE1, or their union, with respect to subsequent 4DCTs and the CTV, coupled with increasing margin. Results: (A) No recalculation exceeded the D1% constraint. (B) The inclusion of RE1 -0Ex in the optimization problem improved inter-fraction robustness on a patient-specific basis, but was non-significant on average. (C) Half of the plans would be re-optimized to recover target coverage and/or minimize duodenum dose, at least once. A significant difference was observed between pre-RT duodenum contours when intersecting subsequent contours, either with a margin expansion. Conclusion: Anatomical variations highlighted at multiple REi proved that a fast and efficient online adaptation is essential to optimize treatment quality of CIRT for pancreatic cancer.